Pengaruh Kemandirian Belajar dan Resiliensi Matematis terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Lina Lutfiyana; Dyan Falasifa Tsani; Mohamad Tafrikan (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
This study aims to determine whether there is a significant effect between learning independence and mathematical resilience simultaneously on the mathematical problem solving ability of eighth grade students of SMP Manbaul Hikmah. The type of research used is quantitative research with survey method. The population in this study were all eighth grade students of SMP Manbaul Hikmah with a research sample of 48 students. The results showed that there was a significant effect between learning independence and mathematical resilience simultaneously on the mathematical problem solving abilities of eighth grade students of SMP Manbaul Hikmah on the Pythagorean which was indicated by the F test results obtained by the value of F_hitung=8,454>3,20. The influence of learning independence and mathematical resilience simultaneously can affect the mathematical problem solving ability of eighth grade students of SMP Manbaul Hikmah by 27.35% and the remaining 72.65% is influenced by other factors not explained in the study.